Coarctation of aorta with special reference to infants. Long-term results of operation in 126 cases. Issue 11 (November 1977) - Patel, R; Singh, S P; Abrams, L; Roberts, K D
Abstract : A review of 126 cases of coarctation of the aorta confirms the need for surgical resection in infants with intractable congestive cardiac failure. The high association with additional cardiovascular abnormalities in patients presenting in early infancy contributes significantly to the mortality. Patients with large ventricular septal defects and coarctation of the aorta are at risk and may require pulmonary artery banding at the time of resection of the aortic coarctation. Long-term complications included restenosis (18 cases) and persistent hypertension (10 cases). In order to prevent persistent hypertension, it is suggested that elective resection of the coarctation be done at 1 year of age.